2016
DOI: 10.1371/journal.pone.0149623
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Practices of Community Pharmacists towards Antimicrobial Stewardship in the State of Selangor, Malaysia

Abstract: BackgroundIncreasing antimicrobial resistance is one of the pressing concerns globally. Injudicious use of antibiotics is one of the modifiable factors responsible for antimicrobial resistance. Given the widespread use of antimicrobials in community settings, pharmacists have an important role in ensuring appropriate use of antibiotics. The objective of this study was to assess the perception and self-reported practices of community pharmacists towards antimicrobial stewardship.MethodsA cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
80
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 28 publications
19
80
4
Order By: Relevance
“…This finding is lower than the result (52.7%) of Khan et al (2016) among community pharmacists in Malaysia. It is very disturbing that more than one-third (35.4%) of the respondents perceived that ABS is aimed at increasing the use of broad-spectrum antibiotics.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…This finding is lower than the result (52.7%) of Khan et al (2016) among community pharmacists in Malaysia. It is very disturbing that more than one-third (35.4%) of the respondents perceived that ABS is aimed at increasing the use of broad-spectrum antibiotics.…”
Section: Discussioncontrasting
confidence: 80%
“…The health and economic impact of ABR is enormous and dreadful, thus, veterinarians (as key healthcare providers) have been encouraged to hold the responsibility of ABS (principally targeted to reduce antibiotic use and development/spread of ABR) in practice area (Erku, 2016;Khan et al, 2016). The results obtained from this study have demonstrated that the overall level of awareness or knowledge about ABS amongst veterinarians in the study area is very poor (21.4%).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations